Peningkatan Strategi dan Metode Pembelajaran Guru PAI dalam Era Revolusi industri 4.0 - Muliatul Maghfirah; Sri Nurhayati (IAIN Madura, 2020)
The globalization becomes the reason of this theme. This is the flow that cannot be banned to enter Indonesia. The modern development of technology and the starting of the industrial revolution era 4.0 which stressed the digital economy, artificial intelligence, big data, and the robotic system cannot be stopped anymore. Facing this challenge, the teaching and learning activities in school are forced to change, including forming qualified teachers for our future. As we know that a teacher has a big role in education, he is both a facilitator and a guide. These roles give a teacher a bigger responsibility not only to transfer knowledge but also to value teaching. He also needs to facilitate the students to be ready to face the industrial era by giving intensive guidance. Therefore, as teachers, we need to be more creative, selective, and active to accommodate all students’ needs and be more sensitive to the students’ psychological condition. A teacher is not only needed to be good in managing the class but also having good teaching skills, empowering learning sources, understanding students’ emotions, and others. In this program, the facilitator will strengthen the teacher’s skill in using various and updated methods so that it can be made as a reference for teachers of PAI in the high school level.(Pemilihan tema tersebut bermula dari arus globalisasi yang sudah tidak terbendung masuk ke Indonesia. Disertai dengan perkembangan teknologi yang semakin canggih, dunia kini memasuki era revolusi industri 4.0, yakni menekankan pada pola digital economy, artificial intelligence, big data, dan robotic. Menghadapi tantangan tersebut, pengajaran di sekolah pun dituntut untuk berubah, termasuk dalam menghasilkan guru berkualitas bagi generasi masa depan. Mengingat posisi pendidik yang sangat signifikan sebagai fasilitator dan pembimbing, maka dari sini sesungguhnya pendidik memiliki tugas yang lebih berat tidak hanya memegang fungsi transfer pengetahuan akan tetapi pendidik juga harus mampu menfasilitasi siswa dalam mengembangkan dirinya disertai dengan bimbingan yang intensif. Oleh karena itu pendidik dituntut untuk lebih kreatif, selektif, dan proaktif dalam mengakomodir kebutuhan siswa guru juga lebih peka terhadap karakteristik maupun psikis siswa. Guru bukan hanya dituntut untuk bisa menguasai teknik pengelolahan kelas, keterampilan, mengajar, pemanfaatan sumber belajar, penguasaan emosional siswa, penguasaan kondisi kelas dan sebagainya. Dalam pengabdian masyarakat ini akan dimantapkan penerapan metode pengajaran yang lebih bervariasi dan terkini sehingga bisa menjadi bahan referensi kepada guru- guru PAI tingkat sekolah menengah pertama dalam mengajar).